The Impact of Reduction SMES Tax on The SMES Growth Case Study in Padang City - Yuli Ardiany; Melli Herfina; Sri Yuli Ayu Putri (EAJ (Economic and Accounting Journal), 2020)
In 2018 the government agreed to only reduce the tax rate to 0.5 percent. This provision is stated in Government Regulation 23/2018. The purpose of this study is to look at the impact of reducing SMEs tax rates on the growth of SMEs in the city of Padang. This type of research is comparative. Data collection techniques in this study are documentation techniques. The population in this study is the SMEs of Padang City the sampling method is purposive sampling. The analytical method used is the analysis of independent sample t-test. The results showed that the average number of SMEs in 2016 and 2017 or before the reduction in tax rates was 31,418.33, where the values in 2016 and 2017 were lower than in 2018 and 2019 at 32,417.33. This shows that there was an increase in the number of SMEs after the reduction in the SMEs tax rate. The significance level of 2- tailed obtained indicates the probability of a significance level of 0.966.